2008
DOI: 10.1086/528934
|View full text |Cite
|
Sign up to set email alerts
|

The Rotational Spectrum of TiO2

Abstract: The rotational spectrum of titanium dioxide (TiO 2 ) has been detected by laser-ablation molecular beam Fourier transform microwave spectroscopy. Thirteen b-type rotational transitions up to J ¼ 9 and K a ¼ 4 were measured for the most abundant isotopic species 48 TiO 2 in the frequency range 7Y42 GHz with accuracies of 1Y10 kHz, allowing for the precise determination of rotational and centrifugal distortion parameters. In addition, eight and six rotational transitions of the rare isotopic species 46 TiO 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
49
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 37 publications
5
49
1
Order By: Relevance
“…Radio astronomers had long sought TiO in the interstellar medium and circumstellar environments (Churchwell et al 1980;Millar et al 1987;Brünken et al 2008), because observations of its rotational lines might yield the temperature and abundances more directly than at optical wavelengths. Although there have been several attempts to observe TiO at radio wavelengths (most with single antennas), all were unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radio astronomers had long sought TiO in the interstellar medium and circumstellar environments (Churchwell et al 1980;Millar et al 1987;Brünken et al 2008), because observations of its rotational lines might yield the temperature and abundances more directly than at optical wavelengths. Although there have been several attempts to observe TiO at radio wavelengths (most with single antennas), all were unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…The rotational spectrum of TiO 2 was first observed in the laboratory when Brünken et al (2008) measured 13 transitions to high accuracy in the centimeter band. Brünken et al determined the rotational and leading centrifugal distortion constants that allow predictions of the astronomically important transitions in the millimeter and submillimeter bands, which subsequent measurements confirmed are accurate to 0.5 km s −1 or better (Kania et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recognized importance of TiO 2 in many research fields, only a few spectroscopic studies on TiO 2 have been reported. 9,10 These spectroscopic studies have provided accurate rotational and vibrational constants and thus geometric parameters for the TiO 2 (X 1 A 1 ) ground state. 9,10 On the theoretical side, predictions on the IE, dissociation energies, molecular geometry, and harmonic vibrational frequencies for TiO 2 (X 1 A 1 ) have also been reported.…”
mentioning
confidence: 99%
“…9,10 These spectroscopic studies have provided accurate rotational and vibrational constants and thus geometric parameters for the TiO 2 (X 1 A 1 ) ground state. 9,10 On the theoretical side, predictions on the IE, dissociation energies, molecular geometry, and harmonic vibrational frequencies for TiO 2 (X 1 A 1 ) have also been reported. [11][12][13] However, up to the present no spectroscopic studies on the TiO 2 + cation have been made, and thus the IE(TiO 2 ) and harmonic vibrational frequencies for TiO 2 + are not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation